Wage Risk, Employment Risk and the Rise in Wage Inequality - Ariel Mecikovsky; Felix Wellschmied (Institute of Labor Economics (IZA), 2016)
We estimate the changes in US male labor market risk over the last three decades in a model of endogenous labor supply and job mobility. Across education groups permanent shocks to productivity have become more dispersed. Moreover, heterogeneity in pay across offered jobs has increased for workers with at least some college education. Simulating these changes in a life-cycle model with search frictions, we show that the estimated changes in risk can account for 85 percent of the increase in within group wage inequality. The welfare costs of rising risk are small.
Keywords: D91; J11; J22; J31; J64; 330; wage risk; secular trends; insurance